Legal Challenges and Recommendations for Strengthening Traditional Medicine Systems in Indonesia - Budiarsih Budiarsih; Amir Amir (IHSA Institute, 2026)
This study analyzes the legal challenges facing traditional medicine practices in Indonesia and formulates normative-based strategic recommendations to address them. Indonesia boasts a rich biodiversity and rich heritage of traditional medicine, but the rapid development of these practices has not been matched by comprehensive regulations, creating a gap between community needs, local wisdom, and legal protection. This study is a normative legal study using both legislative and conceptual approaches. The results identify three main challenges: first, regulatory dualism between the Health Law, the Medical Practice Law, and overlapping regional regulations, creating legal uncertainty and the potential for criminalization of traditional healers. Second, the ambiguous legal status of traditional healers due to voluntary competency standards and licensing, leaving patients without guaranteed safety and practitioners with inadequate legal protection. Third, the weak protection of traditional knowledge in the field of medicine from commercial exploitation without equitable profit sharing. Strategic recommendations include regulatory harmonization through the establishment of a special law for traditional medicine, strengthening the mandatory certification system and national registration, integrating proven safe and effective traditional medicine into the national health system, including the BPJS financing scheme, and increasing the capacity of traditional healers through evidence-based training and collaboration with academics.